2021
DOI: 10.1038/s41467-021-24601-y
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ promotes fibrosis by MYST1-dependent epigenetic regulation of autophagy

Abstract: Activation of fibroblasts is essential for physiological tissue repair. Uncontrolled activation of fibroblasts, however, may lead to tissue fibrosis with organ dysfunction. Although several pathways capable of promoting fibroblast activation and tissue repair have been identified, their interplay in the context of chronic fibrotic diseases remains incompletely understood. Here, we provide evidence that transforming growth factor-β (TGFβ) activates autophagy by an epigenetic mechanism to amplify its profibrotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 94 publications
0
43
0
Order By: Relevance
“…We [14] demonstrated that mice with Atg7 knockout in proximal tubules had fewer atrophic tubules, less apoptosis, and less interstitial fibrosis during UUO. These initial findings are supported by follow-up studies [141][142][143], indicating that autophagy in kidney tubules promotes interstitial fibrosis. Mechanistically, autophagy may induce tubular cell death, cell cycle arrest, and senescence, resulting in the production and secretion of pro-fibrotic and pro-inflammatory cytokines to stimulate fibroblasts for fibrosis [14,138].…”
Section: Autophagy In Tubulointerstitial Fibrosismentioning
confidence: 66%
“…We [14] demonstrated that mice with Atg7 knockout in proximal tubules had fewer atrophic tubules, less apoptosis, and less interstitial fibrosis during UUO. These initial findings are supported by follow-up studies [141][142][143], indicating that autophagy in kidney tubules promotes interstitial fibrosis. Mechanistically, autophagy may induce tubular cell death, cell cycle arrest, and senescence, resulting in the production and secretion of pro-fibrotic and pro-inflammatory cytokines to stimulate fibroblasts for fibrosis [14,138].…”
Section: Autophagy In Tubulointerstitial Fibrosismentioning
confidence: 66%
“…Fibroblasts are quiescent and are exposed to lower oxygen tension and different endogenous factors, but their ability to proliferate and respond to stress may be an important component of skin aging. Many earlier studies used ex vivo primary fibroblasts to identify molecules affecting the progression of diseases, highlighting the value of this cell model (e.g., Katarkar et al., 2020 ; Zehender et al., 2021 ). Future studies in vivo will be needed to complement the collective results gained from cell culture.…”
Section: Discussionmentioning
confidence: 99%
“…In our proteomic analysis, the levels of MCM proteins were significantly lower with age (Figure 6a), potentially underscoring the importance of this protein family in DNA metabolism in chronological skin aging. Zehender et al, 2021). Future studies in vivo will be needed to complement the collective results gained from cell culture.…”
Section: Pathways Less Active In Primary Skin Fibroblasts From Older ...mentioning
confidence: 99%
“…Autophagy is a key intracellular degradation process during which eukaryotic cells clear up harmful or unwanted cytoplasmic contents to maintain cellular homeostasis (49)(50)(51). Current research demonstrates that many factors are involved in modulating this process (19,28,(52)(53)(54). Among them, CDK5RAP3 is reported to regulate autophagy in a renal cancer model (28).…”
Section: Cdk5rap3 As a Potential Participant In Autophagymentioning
confidence: 99%